Pemanfaatan Website Sebagai Media Promosi Digital Bagi UMKM Lokal - Muh.Arfah Wahlil Pratama; Abel Abel; Rika Wulandari; Nurfadilla Nurfadilla; Said Alkhudri; Amsar Diath Yogmar; Supriadi Supriadi (Plexi Digital Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy through their contribution to Gross Domestic Product (GDP) and employment generation. However, many local MSMEs still rely heavily on third-party digital platforms for promotion, limiting their control over brand identity, customer data, and long-term marketing sustainability. Therefore, this study aims to examine the role of websites as strategic digital promotional media for local MSMEs based on the concepts of Marketing 4.0 and the Technology Acceptance Model (TAM). This study employs a descriptive qualitative approach using a Systematic Literature Review (SLR) of scholarly publications published between 2020 and 2025. The findings show that professionally managed websites can increase MSME brand awareness, including brand recognition and brand recall. In addition, previous studies indicate a positive relationship between website utilization and the development of MSME business scale at the local level. Nevertheless, website adoption among MSMEs still faces several challenges, particularly low digital literacy and limited supporting infrastructure. Only a small proportion of MSME actors have reached an advanced level of digital capability. This study concludes that websites can serve as strategic digital assets by enabling independent data management and sustainable search engine optimization (SEO). Furthermore, collaboration between policymakers and academics is necessary to support and accelerate inclusive digital transformation for MSMEs.